2010
DOI: 10.1002/jor.21262
|View full text |Cite
|
Sign up to set email alerts
|

Genetic inactivation of ERK1 and ERK2 in chondrocytes promotes bone growth and enlarges the spinal canal

Abstract: Activating mutations in FGFR3 cause the most common forms of human dwarfism: achondroplasia and thanatophoric dysplasia. In mouse models of achondroplasia, recent studies have implicated the ERK MAPK pathway, a pathway activated by FGFR3, in creating reduced bone growth. Our recent studies have indicated that increased Fgfr3 and ERK MAPK signaling in chondrocytes also causes premature synchondrosis closure in the cranial base and vertebrae, accounting for the sometimes fatal stenosis of the foramen magnum and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 29 publications
(37 reference statements)
4
36
0
Order By: Relevance
“…In cultured chondrocytes, FGFR3 suppression of chondrocyte proliferation required MAPK signaling and was independent of STAT signaling (Raucci et al 2004;Krejci et al 2008a). In support of this observation, mice lacking ERK1 and conditionally lacking ERK2 (Col2a1-Cre) in chondrocytes showed increased chondrocyte proliferation at late embryonic stages (Matsushita et al 2009a;Sebastian et al 2011). Some of the variability in experimental results may be due to in vitro culture conditions, the developmental stage being examined (embryonic vs. postnatal), and potential indirect effects on proliferating chondrocytes resulting from interactions with other signaling pathways in nearby cells within the groove of Ranvier, ring of LaCroix, and perichondrium.…”
Section: Intramembranous Mesenchymal Condensationsmentioning
confidence: 81%
“…In cultured chondrocytes, FGFR3 suppression of chondrocyte proliferation required MAPK signaling and was independent of STAT signaling (Raucci et al 2004;Krejci et al 2008a). In support of this observation, mice lacking ERK1 and conditionally lacking ERK2 (Col2a1-Cre) in chondrocytes showed increased chondrocyte proliferation at late embryonic stages (Matsushita et al 2009a;Sebastian et al 2011). Some of the variability in experimental results may be due to in vitro culture conditions, the developmental stage being examined (embryonic vs. postnatal), and potential indirect effects on proliferating chondrocytes resulting from interactions with other signaling pathways in nearby cells within the groove of Ranvier, ring of LaCroix, and perichondrium.…”
Section: Intramembranous Mesenchymal Condensationsmentioning
confidence: 81%
“…We have also shown that ERK1 and ERK2 inactivation in chondrocytes promotes bone growth. We found increased length of the proximal long bones, specifically the humerus and femur, of ERK1 -/-; ERK2 flox/flox ; Col2a1-Cre embryos (Sebastian et al, 2011). These embryos also showed an increase in the width of epiphyses in the humerus and femur.…”
Section: Erk1 and Erk2 Inhibit Growth Of Cartilaginous Skeletal Elementmentioning
confidence: 61%
“…ERK1 -/-; ERK2 flox/flox ; Col2a1-Cre mutant mice died immediately after birth, likely secondary to respiratory insufficiency caused by rib cage deformity (Matsushita et al, 2009a). To circumvent the perinatal lethality, we also used the Col2a1-CreER transgene to express a tamoxifen-inducible form of Cre recombinase and examined the role of ERK1 and ERK2 in chondrocytes during postnatal growth (Nakamura et al, 2006;Sebastian et al, 2011). For the gain-of-function experiments, we generated Col2a1-MEK1 transgenic mice that express a constitutively active mutant of MEK1 in chondrocytes under the control of the regulatory sequences of Col2a1 (Murakami et al, 2004).…”
Section: Inactivation Of Erk1 and Erk2 In Chondrocytes Causes Severe mentioning
confidence: 99%
See 2 more Smart Citations